2011
DOI: 10.1016/j.juro.2011.03.105
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Urodynamic Predictors of Treatment Failure 1 Year After Mid Urethral Sling Surgery

Abstract: Purpose We determined whether baseline urodynamic study variables predict failure after midurethral sling surgery. Materials and Methods Pre-operative urodynamic study variables and post operative continence status were analyzed from women participating in a randomized trial comparing retropubic to transobturator midurethral sling. Objective failure was defined by positive standardized stress test, or 15 ml or greater on 24-hour pad test, or re-treatment for stress urinary incontinence (SUI). Subjective fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 23 publications
3
44
2
2
Order By: Relevance
“…It has been demonstrated that women with MUCP in the lowest quartile are likely to experience failure of mid urethral sling surgery (17) and that MUCP  40 cm H 2 0 is a risk factor affecting cure after transobturator tape procedure (5).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that women with MUCP in the lowest quartile are likely to experience failure of mid urethral sling surgery (17) and that MUCP  40 cm H 2 0 is a risk factor affecting cure after transobturator tape procedure (5).…”
Section: Discussionmentioning
confidence: 99%
“…In the SISTEr trial, women with USI had better treatment outcomes [11] than women who only demonstrated the sign of SUI but did not have USI. However, in the more relevant trial of midurethral slings (TOMUS), which is the most common surgical treatment offered today, women with USI had worse treatment outcomes than women with the sign of SUI but without USI [12]. Therefore, when stress incontinence is the predominant complaint and it is demonstrable on office evaluation, urodynamic confirmation of this condition adds no apparent benefit to improving outcomes.…”
Section: Confirming the Diagnosis Of Stress Urinary Incontinencementioning
confidence: 99%
“…Markedly different MUCP values are obtained with different measuring technologies [18]. Receiver operator curve outcome data do not suggest there is a biological rationale for cut-off or threshold values for these measures [12]. A recent editorial titled "Intrinsic sphincter deficiency: what is it and does it matter anymore?"…”
Section: Evaluation Of Urethral Functionmentioning
confidence: 99%
“…Investigators have, for example, identified MUCP as a predictor of failure of midurethral slings. 7 Furthermore, understanding the factors affecting urethral closure may lead to novel treatments targeting the urethra. …”
Section: Implications For Treatmentmentioning
confidence: 99%